Brainstem evoked response audiometry in normal hearing subjects - Esteves,Maria Carolina Braga Norte (2009)
Brainstem Evoked Response Audiometry (BERA) is an objective and non-invasive method of hearing assessment which detects electrical activity from the inner ear to the inferior colliculus. AIM: To assess the hearing pathway in normal hearing individuals and compare differences associated with gender, age and ear side (left and right). Study Design: A retrospective study. MATERIALS AND METHODS: Sixty normal hearing individuals, aged between 09 and 66 years old, were subjected to clinical ENT examination and audiologic tests. RESULTS: Wave latencies differed significantly between males and females, although there were no differences regarding right or left ear sides. Comparing latency averages regarding age and gender we noticed important differences. By the same token, significant differences were also seen comparing this study with the information present in the handbook of the BERA device used and results published by Fukuda, in another study. CONCLUSION: Knowing the great importance of BERA, it is crucial that each service develops its own standards in order to enhance the accuracy of the electrophysiological diagnosis of the hearing pathway.